ADA and the Religious Community: The Moral Case - Betenbaugh, Helen R. (Journal of religion in disability & rehabilitation, 1996)
The religious community is technically exempt from the Americans with Disabilities Act of 1990. But is this an acceptable position for places of worship? This article examines the issues not in legal context but in terms of theology, moral teachings, experience and social justice. The author, a person with a disability, concludes with her own constructive theology.